FIRST RECORD OF DREPANOSIPHONIELLA FUGANS REMAUDIЀRE & LECLANT (HEMIPTERA: APHIDIDAE: DREPANOSIPHINAE) ON THE BALKAN PENINSULA (Acta Entomologica Serbica, 2023)
Apterous viviparous females, an alate female, males, and oviparous females of Drepanosiphoniella fugans Remaudiѐre & Leclant, 1972 (Hemiptera: Aphididae: Drepanosiphinae) were found in eastern Serbia (Bor, Zaječar, Stara Planina) in 2022. Drepanosiphoniella is a new genus for Serbia and the Balkan Peninsula. D. fugans is a holocyclic and monoecious species on Acer monspessulanum L. Its main morphological and biological characteristics and distribution are given. A photograph of the apterous viviparous female, line drawings, and slide photographs of the apterous viviparous female, alate viviparous female, oviparous female, and male are also included.